1983
DOI: 10.1093/ajcn/37.2.233
|View full text |Cite
|
Sign up to set email alerts
|

Alimentary lipemia: plasma high-density lipoproteins and apolipoproteins CII and CIII in healthy subjects

Abstract: Three healthy male and three female inpatient volunteers consumed isocaloric diets for 4 wk. At weekly intervals, a fatty meal (100 g fat) was consumed by each fasting subject and blood drawn at 2 h intervals for 12 h. Of the four oral fat loads, two contained saturated fat (polyunsaturated/saturated fat ratio = 0.34) and two contained unsaturated fat (polyunsaturated/saturated fat = 2.21). The magnitude of alimentary lipemia, expressed as area under the plasma triglyceride curve, was 3- to 4-fold higher in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
11
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 36 publications
6
11
0
Order By: Relevance
“…38 - 39 A relative deficiency of apolipoprotein C-II in the HDL fraction might be a limiting mechanism for lipolytic removal of postprandial TGRL triglycerides. This hypothesis is in good agreement with the results from a study by Kashyap et al 40 They found that the response and reciprocal changes of apolipoprotein C-II in HDL and TGRLs in healthy individuals who are given an oral fat load substantiated the notion that apolipoprotein C-II might be of regulatory importance in the removal of postprandial TGRLs. It is also noteworthy that a recent study of endurance-trained men, whose HDL cholesterol levels were well above the distribution in the general population, failed to demonstrate a relation between the fasting HDL cholesterol or its larger subspecies and the response of TGRLs after an oral fat load.…”
Section: Discussionsupporting
confidence: 91%
“…38 - 39 A relative deficiency of apolipoprotein C-II in the HDL fraction might be a limiting mechanism for lipolytic removal of postprandial TGRL triglycerides. This hypothesis is in good agreement with the results from a study by Kashyap et al 40 They found that the response and reciprocal changes of apolipoprotein C-II in HDL and TGRLs in healthy individuals who are given an oral fat load substantiated the notion that apolipoprotein C-II might be of regulatory importance in the removal of postprandial TGRLs. It is also noteworthy that a recent study of endurance-trained men, whose HDL cholesterol levels were well above the distribution in the general population, failed to demonstrate a relation between the fasting HDL cholesterol or its larger subspecies and the response of TGRLs after an oral fat load.…”
Section: Discussionsupporting
confidence: 91%
“…It is known that exogenous and endogenous triglyceride-rich lipoproteins compete for the same clearance mechanism (63). Previous studies of our own using the vitamin A-fat tolerance test (32) and of others using different methods have indeed shown high positive correlations between fasting triglyceride and postprandial lipoprotein levels (64)(65)(66). In this study, fasting triglyceride levels were highest on the SFA diet and lower on the PUFA diets.…”
Section: Discussionsupporting
confidence: 67%
“…After adjusting for higher postabsorptive plasma triglycerides in the apo E4 group by expressing data as a percent change from postabsorptive values, the investigators found that the triglyceride response was reversed and lowest in individuals with apo E4/3 and E4/4 phenotypes. The validity of such an adjustment, which is based upon the assumption that the relationship between the postabsorptive and postprandial response in plasma triglycerides is linear (37)(38)(39), is uncertain because adjustments were also made to account for differences in triglyceride concentrations produced by olive and fish oil supplementation of their diets. Whether the increased postprandial response and delayed peak in retinyl esters in S f Ͼ 1,000 chylomicrons or S f Ͻ 1,000 remnant particles was related only to the higher postabsorptive plasma triglycerides in their apo E4 group is also unclear as the linearity of the relationship between these variables is not well established (6,40).…”
Section: Discussionmentioning
confidence: 99%